Nanostructured Lipid Carriers Loaded with Lippia sidoides Essential Oil as a Strategy to Combat the Multidrug-Resistant Candida auris - Iara Baldim; Mario H. Paziani; Patrícia H. Grizante Barião; Marcia R. von Zeska Kress; Wanderley P. Oliveira (MDPI AG, 2022)
The emerging pathogen Candida auris is an emerging fungal pathogen that was associated with nosocomial infectious outbreaks. Its worldwide incidence and the emerging multidrug-resistant strains highlight the urgency for novel and effective antifungal treatment strategies. Lippia sidoides essential oil (LSEO) proved antifungal activity, including anti-Candida. However, it may undergo irreversible changes when in contact with external agents without adequate protection. Herein, we encapsulated LSEO in nanostructured lipid carriers (NLC) through the hot emulsification method followed by sonication. NLC matrix was based on oleic acid and Compritol® 888, or a combination of carnauba wax and beeswax, stabilized by sodium dodecyl sulfate. Eight formulations were produced and characterized by the determination of the particle size (213.1 to 445.5 nm), polydispersity index (around 0.3), and ζ-potential (−93.1 to −63.8 mV). The antifungal activity of nanoparticles and LSEO against C. auris and the in vivo toxicity in Galleria mellonella model were also evaluated. Both NLC and LSEO exhibited potent activity against the yeast, with Minimum Inhibitory Concentration between 281 and 563 µg/mL, and did not evidence toxicity in the in vivo model. Therefore, this study confirms the viability of NLCs loaded with LSEO in combating drug-resistant pathogens as a potential new therapeutic strategy for managing of candidemia.